2011
DOI: 10.1111/j.1939-165x.2011.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of measuring plasma N‐terminal pro‐brain natriuretic peptide in detecting hypertrophic cardiomyopathy and differentiating grades of severity in cats

Abstract: NT-proBNP with a cut-off value of >100 pmol/L was useful in detecting even mild HCM. Cats with increased NT-proBNP concentrations should be examined by echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 44 publications
6
71
5
Order By: Relevance
“…The second‐generation quantitative plate ELISA used in our study had sensitivity and specificity (84.6 and 100%) similar to previously reported values (sensitivity, 71–92%; specificity, 78–100%) for both the first‐ and second‐generation quantitative assays . The POC ELISA had a lower sensitivity (65.4%) and higher specificity (100%) than previously reported (83.4 and 82.6%) .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The second‐generation quantitative plate ELISA used in our study had sensitivity and specificity (84.6 and 100%) similar to previously reported values (sensitivity, 71–92%; specificity, 78–100%) for both the first‐ and second‐generation quantitative assays . The POC ELISA had a lower sensitivity (65.4%) and higher specificity (100%) than previously reported (83.4 and 82.6%) .…”
Section: Discussionsupporting
confidence: 87%
“…The study found that the percentage of cats with positive POC ELISA results increased as the severity of cardiac disease increased (normal [11.3%], equivocal [12.5%], mild [24%], moderate [83.9%], and severe [83.3%]) . Several other studies have evaluated the ability of the quantitative NT‐proBNP to distinguish among different grades or severity of cardiomyopathy . In these studies, cats with severe cardiomyopathy had significantly higher NT‐proBNP concentrations than did those with mild cardiomyopathy, and NT‐proBNP was found to be less accurate at identifying mild grades of disease, with more false‐negative results than false‐positive results .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific assays have therefore been developed to measure these NP in the different species [43,44]. Also, in dogs and cats, NPs have been found to be useful to distinguish CHF from respiratory disease [43,[46][47][48][49] and increased plasma concentrations of NPs have been identified in dogs with DCM [50-54] and cats with HCM [48,49,[55][56][57]. Also, in dogs and cats, NPs have been found to be useful to distinguish CHF from respiratory disease [43,[46][47][48][49] and increased plasma concentrations of NPs have been identified in dogs with DCM [50-54] and cats with HCM [48,49,[55][56][57].…”
Section: Natriuretic Peptides As Cardiac Biomarkersmentioning
confidence: 99%
“…10 NT-proBNP is released in proportion to the amount of stretch and stress on the myocardium, and the concentration is often increased in cats with heart disease relative to cats without. 8,12 The first-generation feline NT-proBNP immunoassay a provided linear quantitative measurement of NT-proBNP in ethylenediamine tetra-acetic acid (EDTA) plasma samples in a range of 24-1,500 pmol/L, with intra-and interassay precision (%CV) of <15% at points across that range. 8 Sample handling limitations were placed on the assay due to the labile nature of NT-proBNP at room temperature.…”
Section: Introductionmentioning
confidence: 99%